Epistaxis health disparities in the United States pediatric population. (November 2018) - Yang, Lindsay; Hur, Kevin; Koempel, Jeffrey; Ference, Elisabeth H.
Abstract: Objective: Despite epistaxis occurring in up to 60% of the population, few studies have investigated health status disparities in the pediatric epistaxis population. The aim of this study was to evaluate sociodemographic risk factors associated with epistaxis visits for pediatric patients. Methods: Data were extracted from the National Ambulatory Medical Care Survey and National Hospital Ambulatory Medical Care Survey Outpatient Department from 2001 to 2010. Outpatient visits of children less than 18 years who received a primary, secondary, or tertiary diagnosis of epistaxis (ICD-9CM code 784.7X) were included. Bivariate and stepwise multivariate regressions were conducted to develop a final model for epistaxis visits described by sociodemographics. Results: Epistaxis visits accounted for 5 ± 0.6 million visits in children less than 18 years. 51% and 33% of children presenting with epistaxis had private insurance and Medicaid, respectively (p = 0.001). 69% of epistaxis visits were evaluated at a pediatric clinic, 18% at an ENT/surgery clinic, and 13% at a general/family medicine clinic (p < 0.0001). After multivariate adjustment, epistaxis visits were associated with older age (p = 0.006). Black children were more likely to present with epistaxis (95% CI 1.3–4.1, p = 0.005) compared to white children. Allergic rhinitis, present in 11% of epistaxis visits, was a significant comorbidity associated with visits (95%CI 1.3–4.6, p = 0.008). Patients were also more likely to present to an ENT/surgery clinic (95% CI 4.5–16.5, p < 0.0001) compared to a general/family medicine clinic. Conclusions: Epistaxis visits by children are associated with age, race, and specialty. Targeted interventions to help reduce this common presentation should be developed.